2015
DOI: 10.1002/anie.201507568
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Group 15 Monolayers: A Broad Range of Band Gaps and High Carrier Mobilities

Abstract: Optoelectronic applications require materials both responsive to objective photons and able to transfer carriers, so new two-dimensional (2D) semiconductors with appropriate band gaps and high mobilities are highly desired. A broad range of band gaps and high mobilities of a 2D semiconductor family, composed of monolayer of Group 15 elements (phosphorene, arsenene, antimonene, bismuthene) is presented. The calculated binding energies and phonon band dispersions of 2D Group 15 allotropes exhibit thermodynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
347
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 677 publications
(372 citation statements)
references
References 40 publications
22
347
1
2
Order By: Relevance
“…Bi pm ×487 pm. These values agree well with the result of our calculations and existing literature values [17,22,23,25,34,[37][38][39]. Refer to supplementary table SI for full details, including experimental uncertainties.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Bi pm ×487 pm. These values agree well with the result of our calculations and existing literature values [17,22,23,25,34,[37][38][39]. Refer to supplementary table SI for full details, including experimental uncertainties.…”
Section: Resultssupporting
confidence: 92%
“…In our experiments Bi nanoislands (which have been intensively studied previously [16,[30][31][32][33][34]) serve as a basis for the growth of the antimonenes. For growing those Bi islands we have used MoS 2 substrates as well as the more usual graphite (HOPG) and obtain qualitatively similar results in both cases, but focus here on the MoS 2 samples for three different reasons: (i) MoS 2 is a semiconductor which provides opportunities for fabrication of electronic devices, (ii) the difference in the interactions between the Bi and the MoS 2 (compared to HOPG) lead to subtle but interesting structural differences, and (iii) neither antimonene nor bismuthene have been reported on MoS 2 before.…”
Section: Methodsmentioning
confidence: 99%
“…From detailed analysis of the Raman spectra and the corresponding vibrational modes of α-GeSe (see in Fig. 5b), which belongs to the C 2V point group, the Raman ac- 3 1 , atoms belonging to the same species vibrate along opposite directions. Our measurements reveal that the most prominent Raman peaks for β-GeSe, γ-GeSe, δ-GeSe, and ε-GeSe are located at 272.9, 229.4, 77.6, and 50.6 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To search for the ground state of the systems interested here, we must leave from PBE functional because previous studies have shown that PBE for black phosphorus and black arsenic cannot give a reliable prediction. 7,22 The key is that the electron-electron correlation is underestimated by PBE, we therefore turn to the investigations by HSE06. Within HSE06, the increase of magnetic moments and band gaps are obvious, while the total energy also gets more efficient reduction.…”
Section: Nanoribbons (Zvnrs)mentioning
confidence: 99%
“…8 In this area, magnetic elements are usually used to dope and substitute in the semiconductor. In consideration of the magnetism appearing at the edges of two-dimensional materials, such as graphene, 9,10 MoS 2 , 11 and ZnO 12 hence we turn to study the edged magnetism in one-dimensional zigzag Puckered group V monolayer (Vene) 7 …”
mentioning
confidence: 99%